VD_FINDINFO Jug / 2024 / 320 vom 16. November 2023 - VD Tribunal cantonal (2023)
LÉSION CORPORELLE GRAVE, MISE EN ACCUSATION, PRINCIPE DE L'ACCUSATION | 122 CP, 47 CP, 325 al. 1 let. f CPP (CH), 333 CPP (CH), 9 CPP (CH)